ANALISIS DAERAH RAWAN GENANGAN PADA RUAS JALAN SAPTA MARGA KOTA PALEMBANG DENGAN SIMULASI EPA SWMM 5.1 - Marlina, Ayu; Andayani, Reni; Permatasari, Rosmalinda; Pahrizal, Pahrizal (LATERAL: Jurnal Teknik Sipil, 2024)
Palembang city has an area of 400.61 Km2 and is divided into 19 sub-watersheds that flow into the Musi river. One of the sub-watersheds in Palembang city is Buah Sub-watershed with an area of 10.79 Km2.The study area is located at Sapta Marga Street, Kelurahan Bukit Sangkal, Kecamatan Kalidoni, Palembang City.The purpose of this study was to determine the condition of the existing secondary drainage channel on Sapta Marga road, determine the peak discharge in the Buah Sub Watershed, make new drainage dimension planning for the study area and simulate new drainage after recalculating the dimensions with the EPA SWMM 5.1 program. Primary data in this study are the dimensions and length of existing channels, channel slope data taken using theodolite tools. Secondary data is rainfall data from the BMKG station for 5 years and land use data. Peak discharge is calculated by the Rational method. The results of this study obtained the condition of the existing secondary drainage channel on Jalan Sapta Marga, with channel dimensions of 0.3 m x 0.3 m with a square cross section, runoff occurs at STA 1045 - STA 1195. The peak discharge (Qh) in Sub Watershed Buah, with an area of 77.45 ha River Drainage Area (DPS) is 0.20 m3 /s. Planning new secondary drainage dimensions to be able to accommodate peak discharge in the study area with new dimensions of width (B) 0.65 m, height (h) 0.65 m, and freeboard (f) 0.45 m. The results of the new drainage simulation using the EPA SWMM 5.1 program secondary channels do not runoff.